Characterization and evolution of dermal filaments from patients with Morgellons disease - Middelveen MJ; Mayne PJ; Kahn DG; Stricker RB (Dove Medical Press, 2013)
Marianne J Middelveen,1 Peter J Mayne,1 Douglas G Kahn,2 Raphael B Stricker11International Lyme and Associated Diseases Society, Bethesda, MD, USA; 2Department of Pathology, Olive View–UCLA Medical Center, Sylmar, CA, USAAbstract: Morgellons disease is an emerging skin disease characterized by formation of dermal filaments associated with multisystemic symptoms and tick-borne illness. Some clinicians hypothesize that these often colorful dermal filaments are textile fibers, either self-implanted by patients or accidentally adhering to lesions, and conclude that patients with this disease have delusions of infestation. We present histological observations and electron microscopic imaging from representative Morgellons disease samples revealing that dermal filaments in these cases are keratin and collagen in composition and result from proliferation and activation of keratinocytes and fibroblasts in the epidermis. Spirochetes were detected in the dermatological specimens from our study patients, providing evidence that Morgellons disease is associated with an infectious process.Keywords: Morgellons disease, digital dermatitis, Lyme disease, Borrelia burgdorferi, spirochetes, keratin, keratinocytes, collagen, fibroblasts